2015
DOI: 10.1111/pai.12422
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of animal component sensitization, asthma, and rhinitis in schoolchildren

Abstract: Among schoolchildren in northern Sweden, where mite allergy is uncommon, furry animals were the primary perennial sensitizers. Asthma was associated with higher levels of component sensitization, and sensitization to more than one component from the same animal conferred the greatest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
80
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 30 publications
13
80
2
3
Order By: Relevance
“…They stated the importance of identifying specific allergen components associated with asthma and severe disease. Bjerg et al reported a higher prevalence of asthma in children co-sensitized to rFel d1 and rFel d 4 than in children sensitized to r Fel d 1 alone [50]. We also saw a higher prevalence of reported asthma (55%) in patients with IgE reactivity, not only toward rFel d 1, but also toward nFel d 2 and/or rFel d 4.…”
Section: Discussionsupporting
confidence: 59%
“…They stated the importance of identifying specific allergen components associated with asthma and severe disease. Bjerg et al reported a higher prevalence of asthma in children co-sensitized to rFel d1 and rFel d 4 than in children sensitized to r Fel d 1 alone [50]. We also saw a higher prevalence of reported asthma (55%) in patients with IgE reactivity, not only toward rFel d 1, but also toward nFel d 2 and/or rFel d 4.…”
Section: Discussionsupporting
confidence: 59%
“…A study by Bjerg et al [5] found sensitization to the Fel d 1 component in 83.7% of its research group, which comprised of 208 children aged 11–12 sensitized to felines. In that group monosensitization was found in 67.8% of patients [5]. …”
Section: Discussionmentioning
confidence: 99%
“…The levels of IgE were evaluated as heightened when they exceeded 0.35 kU/l, in accordance with common practice in the field [5, 6]. …”
Section: Methods and Research Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitization also differs by sociodemographic factors, including age, gender, race/ethnicity and socioeconomic status [51]. Novel data on sensitization patterns have emerged from recent studies that have used component-resolved diagnostics to increase knowledge on sensitization profiles and cross-reactivity [28, 49, 54, 55]. Numerous studies have demonstrated that sensitization, especially high pet-specific IgE levels and co-sensitization, are strongly associated with the prevalence, severity and persistence of asthma [5, 26, 49, 54, 5658].…”
Section: Bedroom Allergen Exposuresmentioning
confidence: 99%